Usability research for interpreter-centred technology The case study of SmarTerp - Frittella, Francesca Maria (Language Science Press, 2023)
Technological advancement is reshaping the ways in which language interpreters operate. This poses existential challenges to the profession but also offers new opportunities. This books moves from the design of the computer-assisted interpreting tool SmarTerp as a case study of impact-driven interpreting technology research. It demonstrates how usability testing was used to achieve an interpreter-centred design. By contextualising the case study within the past and current developments of translation and interpreting technology research, this book seeks to inform and inspire a redefinition of the conceptualisation of interpreting technology research-not just as a tool to understand change but to drive it into a sustainable and human direction.